The Phenomenon of Poetry as Arabic Culture on Twitter - Azhar Ismail Hasibuan; Andi Holilullah (Nady Al-Adab : Jurnal Bahasa Arab, 2023)
Abstrak: This paper focuses on the development of Arabic poetry from the Jahiliyah period (using makeshift media) and the Contemporary period (using Twitter media) for poetry, as well as the ideas and thoughts of Arabic writers in the poem. Through a historical-diachronic study of the medium of Arabic poetry during the Jahiliyah and Contemporary periods, it can be concluded that the culture and tradition of poetry have differences. If during the Jahiliyah period poetry was produced using makeshift media, such as date palm fronds, animal bones, and palm leaves, then in the contemporary era poetry is immortalized through Twitter media. Poetry on Twitter (cyberliterature) is a unique phenomenon that seems to take over the position of printing media. The tradition of poetry became the most popular and popular social practice among literati, social, political, religious and cultural phenomena were raised through poetry. Many contemporary writers share their thoughts and poems on Twitter, however, this study features at least four contemporary figures who participated in Twitter: Najm Al-Husainy, 'Issa Jarȃba, Dalal al-Barudi, and Sa'ud Al-Sanusy. Although poets do not always produce their poems on Twitter, through this activity literati can interact with poetry connoisseurs from various societies in the world.